The power of meaning: the quest for an existential roadmap. Issue 1 (24th May 2018) - Paulson, Steve; Lombard, Jay; Pigliucci, Massimo; Ruse, Michael; Smith, Emily Esfahani
Abstract: Where can we turn to find the story of our lives—an existential roadmap that explains where we have come from, why we are here, and where we are headed? Must each of us discover meaning within the context of our individual lives, or are there universal sources of meaning that we can all access? Is there any relationship between living a meaningful life and the quality of our health and well‐being? And how can we find meaning in the face of adversity and suffering? Neurologist Jay Lombard, philosophers Massimo Pigliucci and Michael Ruse, and author Emily Esfahani Smith shed light on these perennial questions in conversation with Steve Paulson, executive producer and host of To the Best of Our Knowledge .